PUTUSAN MK NOMOR 135/PUU-XXII/2024 DALAM PERSPEKTIF RADBRUCH: TEGANGAN ANTARA KEADILAN DAN LEGALITAS - Anidaul Khanifah; Shanita Nuraini Thaqwim (Jurnal Perspektif Hukum, 2025)
The Constitutional Court Decision No. 135/PUU-XXII/2024 introduces a separation between national and regional elections, allowing for a 2–2.5 year gap. This decision opens up space for the extension of regional executive terms or the extension of the appointment of implementing officials without electoral legitimacy, thus creating a constitutional dilemma between formal legality and substantive justice within the Indonesian legal framework. This research uses a normative juridical method with descriptive-qualitative analysis. The analysis shows that this decision reflects a shift in the role of the Constitutional Court from a negative legislator to a positive legislator, raising concerns about constitutional violations and judicial inconsistencies. Furthermore, when examined using Gustav Radbruch's theory of legal objectives, namely justice, certainty, and benefit, that when viewed from a justice perspective, this decision can cause voter fatigue or voter fatigue which ultimately reduces the quality of political participation and the most problematic impact is extending the term of office of regional heads or the appointment of regional heads. So constitutionally it raises serious concerns regarding violations of Article 22E (1) of the 1945 Constitution which states that elections must be held in a Direct, General, Free, Secret, Honest, and Fair manner, within a period of 5 years. Furthermore, seen from the perspective of legal certainty, this decision opens up room for uncertainty because it requires major revisions to the Election Law and the Regional Election Law. Election organizers such as the KPU and Bawaslu must adjust systems, budgets, and technical regulations that do not yet have a clear operational basis. Then, if seen from the perspective of legal benefits, the separation between National Elections and Regional Elections has the potential to create a greater fiscal burden because the state must organize two electoral processes.